CRYSTALLINE FRAGMENTS IN GLASSES - Antonio, G. A.; Kalia, R. K.; Nakano, A.; Vashishta, P. (American Physical Soc, 1992)
The nature of tetrahedral molecular fragments is investigated in SiSe2 glasses using the molecular-dynamics method. The glass consists of both edge-sharing (ES) and corner-sharing tetrahedra. The ES tetrahedra are the building blocks of chain-like-molecular fragments. The two-edge-sharing tetrahedra are the nucleus, and corner-sharing configurations provide connecting hinges between fragments. Statistics of rings and fragments reveals that threefold and eightfold rings are most abundant, chainlike fragments that are typically 10-15 angstrom long occur mostly in eightfold rings, and the longest fragments occur in elevenfold rings.